Comparative Study of Gandhaka Shodhan by different methods: Array - Salunkhe, Prabhakar Shamrao (Ayurline: International Journal of Research in Indian Medicine, 2020)
It is clear from the observations and inferences that the physical properties like a) Colour, b) Odour, c) Melting Point and d) Chemical properties shows some changes. Possible reasoning for this and its significance is discussed here. Colour :- There are slight changes in colour of Shuddha Gandhaka. It may be due to the different substances used for shodhan as Godugdha and Goghruta. But there is no change in colour of sublimed Gandhaka as it is not treated by any other substance. Odour :- There was notable change in smell of Shuddha Gandhaka which is treated by Godugdha and Goghruta. But sublimed Gandhaka was not treated by any other substance, so its smell remain some. Melting Point :- Changes in melting point of Shuddha Gandhaka were noted. They may be due to adherence of the material used for Shodhana as they are in the form of Carbon. Change in melting point of sublimed Gandhaka can not be defined. It may be due to changes of transition temperature of Gandhaka form as solid to vapours. Elemental Analysis :- Particle size was reduced and there was coating of fats shown as Carbon in Shuddha Gandhaka which was treated by Goghruta and Godugdha. This Gandhaka becomes more effective as per its Vyavai guna. Due to coating it may achieve the target site as per time releasing property.